Adab-Based Pesantren Educational Management, Kiai Leadership, and Organizational Culture: A Study at Pondok Pesantren Ulul Albab Asyadi Madura - Suhertini, Heni; Nugraha, Mulyawan S. (Dinasti Publisher, 2025)
This article is entitled “Adab-Based Pesantren Educational Management, Kiai Leadership, and Organizational Culture: A Study at Pondok Pesantren Ulul Albab Asyadi Madura”. The study is motivated by the importance of pesantren educational management that integrates moral values, exemplary leadership, and organizational culture beyond administrative functions. This research aims to analyze the implementation of adab in educational management, the role of kiai leadership, and their relationship with pesantren organizational culture. The study employed a quantitative approach with a descriptive-analytical design. The research object consisted of members of the educational community at Pondok Pesantren Ulul Albab Asyadi Madura, including the kiai, teachers, and educational staff. Data were collected through questionnaires and analyzed using descriptive statistical techniques. The results indicate that pesantren educational management is categorized as very good, characterized by the strong implementation of adab in educational activities, exemplary kiai leadership in decision-making, and an organizational culture that supports discipline, deliberation, and continuous evaluation. The study concludes that the integration of adab, kiai leadership, and organizational culture plays a crucial role in enhancing the effectiveness of pesantren educational management.